Relationship Between whitefly (Bemisia tabaci) Population and Pepper Yellow Leaf Curl Disease on Chili Plant Yield in The Field - Taufik, Muhammad; Hasan, Asmar; Mallarangeng, Rahayu; HS, Gusnawaty; Khaeruni, Andi; Botek, Muhammad; Syair, Syair (CROPSAVER, 2023)
Whitefly vector insects can spread the Pepper yellow leaf curl Indonesia virus (PYLCIV)  that causes Begomovirus disease. One whitefly can transmit the virus, which belongs to the Begomovirus genus. It is suspected that the more whitefly, the higher the incidence and severity of Begomovirus disease. The increased severity of Begomovirus disease can affect chili yields. This study aimed to assess the relationship between the whitefly population level, the Begomovirus disease's intensity, and the production of chili peppers. The research method used was a survey of the farmers' chili plantations. Observations of the whitefly population and disease intensity were carried out on a scheduled basis. The results showed that the whitefly population affected the incidence and severity of the disease Begomovirus. Each addition of one whitefly/leaf will increase the incidence of disease by 25.981%, the severity by 15.269%, and reduce the yield of chili plants by 40.044 kg/ha. Meanwhile, every 1% increase in the severity of Begomovirus disease will reduce the production of chili plants by 2.867 kg/ha.